Mechanical sandstone deterioration due to cement binder material materials under dry-wet cycling - Fuzhi Wang; Jizhong Huang; Hengyu Zhao (Case Studies in Construction Materials, 2023)
The effects of cementitious materials used in the early conservation of stony cultural heritage on sandstones have yet to be clarified. The impact of cementitious materials on mechanical and physicochemical properties was investigated by designing sandstones for wet and dry cycling in neutral and alkaline solutions (pure water, sodium hydroxide, calcium hydroxide, ordinary cement, and low alkaline cement). The sandstone was examined before and after the wet and dry cycles using X-ray fluorescence spectrometry (XRF), ion chromatography (IC), and X-ray diffractometry (XRD) to characterize the deterioration of the sandstone material caused by cement from macro and micro perspectives and the diffusion characteristics of the soluble components of cement in the sandstone. The results show that the concentration of Ca2+ precipitated within the sandstone after cycling is higher than that of Cl-, SO42-, NO3-, Na+, and K+ and has the most significant influence on the sandstone properties. In terms of mass, there is a 3%−6% mass loss in the sandstone after dry and wet cycling in NaOH solution and a 2%−7% mass accumulation in cement and Ca(OH)2 solution. The cumulative damage (DN) variation pattern of sandstones was also analyzed based on wave velocity variation. The damage rate fluctuated in a wider region of 6%−30% for medium-weathered sandstones subjected to dry and wet cycling in cement solution compared to fresh sandstones, and 9%−20% for fresh sandstones. In addition, it was found that the deterioration process of sandstone by cement materials is physicochemically synergistic, while the macro-mechanical properties correspond closely to the changes in material composition.